Molecular Analysis of Y Chromosome Microdeletions in Oligozoospermic Iraqi Patients - Saud, Asmaa Mohammed; Rasool, Hayder Mazin (Iraqi Journal of Science, 2022)
This study was designed to determine the correlation between Y chromosome azoospermia factor (AZF) subregions microdeletions and oligozoospermia in infertile men. Subjects included 50 infertile men with oligozoospermia who had been referred to the Fertility Center and infertility treatment in Kamal Al-Samarrai Hospitalhealth office-Iraq. DNA was extracted from blood samples. Polymerase chain reaction (PCR) amplification of 3 loci spanning the AZFa, AZFb and AZFc subregions of the Y chromosome using sY84, sY127 and sY254 and were performed. The frequency of deletions involving AZFa subregion of the Y-chromosome was found in twelve of the patients (24%) in oligozoospermic infertile Iraqi men. While the other subregion (AZFb and AZFc) of the Y-chromosome were not determined microdeletion in oligozoospermic samples. The study showed that men with oligozoospermia should be evaluated for Yq11 microdeletionsbefore deciding to operate varicoceles or else scheduling them for assisted reproductive techniques and there is a specific correlation between Y chromosome AZFa subregions microdeletions and oligozoospermia.